Pembaharuan Pendidikan Islam di Indonesia (Studi Pemikiran K.H. Ahmad Dahlan) - Sumarno Sumarno (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2017)
The renewal of Islamic education in Indonesia is inseparable from the character of educational thinkers. This paper deals with the study of the thought of KH. Ahmad Dahlan with the method examines how the concept of Islamic education according to KH. Ahmad Dahlan, KH. Ahmad Dahlan's thinking about how education reform and social theology of Islam, what are the contributions of K.H. Ahmad Dahlan in the world of Islamic education in Indonesia and how relevance thought KH. Ahmad Dahlan in the national education system. The concept of Islamic education is the concept that has a valid epistimologi, because the Foundation or base of Islamic education, educational objectives of Islam, and Islamic educational material, all sourced from the Qur'an and Hadith of  Prophet Muhammad. Similarly, with the aim of education in Muhammadiyah moslem materialize i.e. adopting noble, ably, believe in yourself, as well as useful for the society and the State. The Muhammadiyah movement in the early days of its founding, also enshrined the failed conditions of the people in all fields. Therefore, it is very reasonable if the base with the basic theology of Qur'an surat al-Ma'un, became a cornerstone in settling all its people. Al-Ma'un Charity framework, namely in the form of strengthening and empowering of a wealth of physical, moral, spiritual, economic, social, and environmental. Meanwhile Charity al-Ma'un pillar consists of series of orphaned, to serve the poor, embodying the values of worship (Salat), purifying the intention, steer clear of riya, and build the useful of partnerships.Keywords: Renewal, Islamic Education, Theology, KH. Ahmad Dahlan